φ-Multipliers on Banach Algebras and Topological Modules - Marjan Adib (Abstract and Applied Analysis)
We prove some results concerning Arens regularity and amenability of the Banach algebra MφA of all φ-multipliers on a given Banach algebra A. We also consider φ-multipliers in the general topological module setting and investigate some of their properties. We discuss the φ-strict and φ-uniform topologies on MφA. A characterization of φ-multipliers on L1G-module LpG, where G is a compact group, is given.